2018
DOI: 10.1177/0276237418818637
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Brain Stimulation: An Overview of Available Approaches for Research in Neuroaesthetics

Abstract: Noninvasive brain stimulation methods, like transcranial magnetic stimulation and transcranial electrical stimulation, are largely employed in cognitive neuroscience to investigate brain–behavior relationships. This review offers an overview of mechanisms of actions of transcranial magnetic stimulation and different types of transcranial electrical stimulation and considers recent studies that have shed light on the neural underpinning of aesthetic evaluation of (visual) artworks by means of noninvasive brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 98 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…Since there is no independent biological marker that can be used to identify neurobiological states as beautiful, all such studies rely on subjects reporting whether they experience something as beautiful. On the basis of such evaluations, scientists can ask if beauty responses are elicited by specific perceptual properties and try to chart the neural processes necessary for their generation 2,5,13,14,36 …”
Section: Beauty As a Scientific Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…Since there is no independent biological marker that can be used to identify neurobiological states as beautiful, all such studies rely on subjects reporting whether they experience something as beautiful. On the basis of such evaluations, scientists can ask if beauty responses are elicited by specific perceptual properties and try to chart the neural processes necessary for their generation 2,5,13,14,36 …”
Section: Beauty As a Scientific Problemmentioning
confidence: 99%
“…On the basis of such evaluations, scientists can ask if beauty responses are elicited by specific perceptual properties and try to chart the neural processes necessary for their generation. 2,5,13,14,36 Over the last 150 years, influenced by the philosophical tradition described above, hundreds of behavioral studies have sought to determine which sensory features people find beautiful by systematically manipulating stimulus properties. While these studies have found some stimulus properties to be reliably associated with beauty responses in most people-for example, symmetry or facial averageness in the visual domain; [37][38][39] consonance or expectancy violations in the auditory domain [40][41][42][43] they have also revealed that beauty responses are not fixed.…”
Section: Beauty As a Scientific Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, however, neither psychology nor neurobiology have succeeded in showing how beauty appraisals differ from other forms of sensory appraisal. 10,11 There are several overviews of neuroscientific research on aesthetic appreciation 2,5,[12][13][14] and facial attractiveness. [15][16][17][18] But no review paper has tried to summarize what is known about beauty as a psychological and neurobiological phenomenon per se.…”
mentioning
confidence: 99%